Bone Marrow Derived Mesenchymal Stromal Cells Promote Vascularization and Ciliation in Airway Mucosa Tri-Culture Models in Vitro - Luengen, Anja E.; Cheremkhina, Maria; Gonzalez-Rubio, Julian; Weckauf, Jan; Kniebs, Caroline; Uebner, Hendrik; Buhl, E. Miriam; Taube, Christian; Cornelissen, Christian G.; Schmitz-Rode, Thomas; Jockenhoevel, Stefan; Thiebes, Anja Lena (Frontiers in Bioengineering and Biotechnology, 2022)
Patients suffering from irresectable tracheal stenosis often face limited treatment options associated with low quality of life. To date, an optimal tracheal replacement strategy does not exist. A tissue-engineered tracheal substitute promises to overcome limitations such as implant vascularization, functional mucociliary clearance and mechanical stability. In order to advance a tracheal mucosa model recently developed by our group, we examined different supporting cell types in fibrin-based tri-culture with primary human umbilical vein endothelial cells (HUVEC) and primary human respiratory epithelial cells (HRE). Bone marrow derived mesenchymal stromal cells (BM-MSC), adipose-derived mesenchymal stromal cells (ASC) and human nasal fibroblasts (HNF) were compared regarding their ability to promote mucociliary differentiation and vascularization in vitro. Three dimensional co-cultures of the supporting cell types with either HRE or HUVEC were used as controls. Mucociliary differentiation and formation of vascular-like structures were analyzed by scanning electron microscopy (SEM), periodic acid Schiff’s reaction (PAS reaction), two-photon laser scanning microscopy (TPLSM) and immunohistochemistry. Cytokine levels of vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), interleukin-6 (IL6), interleukin-8 (IL8), angiopoietin 1, angiopoietin 2, fibroblast growth factor basic (FGF-b) and placenta growth factor (PIGF) in media supernatant were investigated using LEGENDplex™ bead-based immunoassay. Epithelial morphology of tri-cultures with BM-MSC most closely resembled native respiratory epithelium with respect to ciliation, mucus production as well as expression and localization of epithelial cell markers pan-cytokeratin, claudin 1, α-tubulin and mucin5AC. This was followed by tri-cultures with HNF, while ASC-supported tri-cultures lacked mucociliary differentiation. For all supporting cell types, a reduced ciliation was observed in tri-cultures compared to the corresponding co-cultures. Although formation of vascular-like structures was confirmed in all cultures, vascular networks in BM-MSC-tri-cultures were found to be more branched and extended. Concentrations of pro-angiogenic and inflammatory cytokines, in particular VEGF and angiopoietin 2, revealed to be reduced in tri-cultures compared to co-cultures. With these results, our study provides an important step towards a vascularized and ciliated tissue-engineered tracheal replacement. Additionally, our tri-culture model may in the future contribute to an improved understanding of cell-cell interactions in diseases associated with impaired mucosal function.